Indonesia's rise in digital democracy and youth's political participation. Issue 4 (2nd October 2021) - Saud, Muhammad; Margono, Hendro
ABSTRACT: The platform of digital media has particularly reshaped the political structure of Indonesia. The public is using social media applications for political participation and an expression of their political opinions. This survey was conducted in Indonesia to examine the impact of digital media among youngsters and their political engagement through digital platforms. The study was influenced by the phenomenon of massive student participation, which occurred in August 2019, in Indonesia as a reaction to a new corruption (KPK) law. The study opted for the public sphere theory of Jürgen Habermas; 'The Public Sphere'. This correlates to the study objective whereby youth participate in political matters to learn and to discuss their common beliefs in the public spheres. The study design is quantitative and more than four hundred respondents were selected during the protests through random sampling techniques. The conclusion of the study demonstrates that youth participate in multiple activities, such as protests for new laws, which indeed strengthen democracy and contribute to the political structure of Indonesia. Therefore, youth participation through social media platforms shows their political participation in Indonesia. The study also suggests a few recommendations for youth to show their participation through online spheres.